Partisipasi Keluarga dalam Tumbuh Kembang Anak dan Remaja sebagai Literasi Pengasuhan Pencegahan Stunting - Fitriani Mediastuti; Reni Tri Lestari (Jurnal Sehat Mandiri, 2024)
The family plays a crucial role in stunting prevention, serving as valuable educators in child development. This study aims to understand the role of family participation in the growth and development of children and adolescents as caregiving education for stunting prevention. The research was conducted in Timbulharjo, Sewon, Bantul, Yogyakarta, from August to September 2023, employing a cross-sectional method. The study population includes parents with children up to 13 years old, using accidental sampling for participant selection. Data analysis was performed using univariate and bivariate methods. The results showed that 76.2% of families have above-average knowledge of stunting prevention efforts. Additionally, 59.5% of families demonstrated a positive attitude, and 64.3% had a positive intention towards stunting prevention. The p-value for the variables of employment status and the number of children concerning the knowledge, attitude, and intention of families in stunting prevention was above 0.05. The conclusion is that the majority of families have positive knowledge, attitudes, and intentions regarding stunting prevention. The findings also indicate no significant influence from educational level, employment status, or number of children on the knowledge, attitudes, and intentions of families in stunting prevention. The study suggests the need for enhanced promotional activities for stunting prevention at the family level, involving various relevant stakeholders. The community should also improve their quality by actively participating in activities organized by the village to prevent stunting.